Factores determinantes de la relación entre la localización de las empresas, la dinámica del transporte público tipo BRT y el desarrollo urbano - Cabrera-Moya, Diego Rafael Roberto (El Colegio de México A.C., 2022)
The literature associated with the new urban geography and with the agglomeration economies theory attempts to explore and explain the relationship of the economic and urban development of cities with their inhabitants and with organizations as essential actors in this interaction. In this sense and as a result of the central objective, the findings of the updated bibliographic review on the problems that arise from the dynamics of interaction between the BRT transport systems, the territory and the decisions of geographical location of the companies are presented. In this way, a specific contribution and current reflection on the relationship between mass public transport, urban space and the role of the foundations of this theory is proposed. This review made it possible to analyze this relationship from its economic, spatial, social and urban dimensions, addressing the main theoretical and empirical proposals available in recent literature. In the second section of the article, a synthesis of the results of the updated and exhaustive review of the empirical bibliography is presented, which starts from the work of Lampón Caride (2011), to propose a framework for the analysis of determining factors on the relationship between location of companies, transport dynamics and urban development. In the final section, an analysis of the problem and interaction between BRT public transport, the territory and the urban economy is presented, analyzed from the perspective of transport oriented development (TOD), exemplified in the systems of Curitiba in Brazil, Bogotá in Colombia, Mexico City and Santiago in Chile. As a main contribution, the existence of a relationship between the territory and the location of the companies is proposed, which in turn is influenced by the dynamics of public transport, mobility, urban development and by the economic evolution of cities, detailing starting from its economic, spatial, social and urban dimensions.